2021
DOI: 10.3390/antibiotics10020188
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Prevalence of Antibiotic Resistance Genes According to the Wastewater Treatment Scale Using Metagenomic Analysis

Abstract: Although extensive efforts have been made to investigate the dynamics of the occurrence and abundance of antibiotic resistance genes (ARGs) in wastewater treatment plants (WWTPs), understanding the acquisition of antibiotic resistance based on the WWTP scale and the potential effects on WWTPs is of relatively less interest. In this study, metagenomic analysis was carried out to investigate whether the WWTP scale could be affected by the prevalence and persistence of ARGs and mobile genetic elements (MGEs). As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 63 publications
1
3
0
Order By: Relevance
“…In this study, one Arr, eleven Erm and two Sul proteins were predicted to have undergone recombination. The arr, erm and sul genes are usually associated with mobile genetic elements such as plasmids, integrons and transposons, which facilitate the dissemination of antibiotic resistance through HGT [51][52][53]. Our results are consistent with those in earlier studies [54,55] that reported Erm proteins to be frequently involved in HGT in grampositive bacteria.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, one Arr, eleven Erm and two Sul proteins were predicted to have undergone recombination. The arr, erm and sul genes are usually associated with mobile genetic elements such as plasmids, integrons and transposons, which facilitate the dissemination of antibiotic resistance through HGT [51][52][53]. Our results are consistent with those in earlier studies [54,55] that reported Erm proteins to be frequently involved in HGT in grampositive bacteria.…”
Section: Discussionsupporting
confidence: 92%
“…The high prevalence of the tetracycline resistance genes (tetQ, tetW, tetM, and tetO) might be the result of antibiotic selective pressure, considering that tetracyclines persist for a long time in the environment and are used frequently in human and veterinary medicine and aquacultural and agricultural practices [44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…Proteobacteria, Chloroflexi, and Acidobacteria were the most abundant under phyla level in the estuaries [10]. Proteobacteria were also the most dominant bacterial phylum in wastewater treatment plants (WWTPs), Tai Lake and Qinghai Lake [13,15,33]. It suggested that Proteobacteria and Actinobacteria appeared to be the main microbial colonizers of natural substrates in aquatic environments [34].…”
Section: Microbial Community Structurementioning
confidence: 98%
“…3B). In previous studies, multidrug was most frequent in urban environments [20], the drinking water supply system [36], estuaries [37], urban-lake drinking water [38], as well as WWTPs [33]. The highest content in the sediment of Tai Lake was the multidrug, followed by macrolidelincosamide-streptogramin (MLS), and bacitracin [15].…”
Section: Args Compositionmentioning
confidence: 99%